NEW METHODS OF TEACHING ENGLISH: TODAY AND TOMORROW (International journal of artificial intelligence, 2025)
This article is devoted to new and effective methods of teaching English. In the current globalization process, English has become an important language in the world, modern teaching methods such as interactive teaching, the use of social media, multimedia technologies and creative approaches, and therefore the need to search for effective methods for learning and teaching it are analyzed. The article considers the theoretical and practical aspects of the new methods of teaching English, as well as methods that help the student develop activity, problem-solving and independence.